(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of an intervention to improve satisfaction with outpatient health insurance medication dispensing among elderly patients at Hai Phong Medical University Hospital in 2025–2026. Methods: A before-and-after interventional study without a control group was conducted among 250 elderly patients before the intervention (TCT) and 250 elderly patients after the intervention (SCT) at the outpatient health insurance pharmacy. Patient satisfaction was assessed using a structured questionnaire covering five domains. Data was analyzed using Excel 2024 and SPSS 26.0. Results: Overall satisfaction increased by 7,6% after the intervention, with an effectiveness index of 9.4% (p=0.019). Satisfaction with pharmacists’ attitude and professional competence increased by 8,0% (p=0.012). The largest improvement was observed in professional competence in medication counseling, which increased by 16,4%(p<0.001). Conclusion: The intervention improved elderly patients’ satisfaction with outpatient health insurance medication dispensing, particularly in communication, counseling, procedural convenience, and transparency of dispensing information.